State Transfer in Noisy Modular Quantum Networks - Hahto, Markku; Piilo, Jyrki; Nokkala, Johannes (John Wiley and Sons Inc, 2025)
Quantum state transfer is the act of transferring quantum information from one system in a quantum network to another without physically transporting carriers of quantum information, but instead engineering a Hamiltonian such that the state of the sender is transferred to the receiver through the dynamics of the whole network. A generalization of quantum state transfer called quantum routing concerns simultaneous transfers between multiple pairs in a quantum network, imposing limitations on its structure. This study considers transfer of Gaussian states over noisy quantum networks with modular structure, which have been identified as a suitable platform for quantum routing. Two noise models are compared, affecting either the network topology or the network constituents, studying their effects on both the transfer fidelities and the network properties. The two models are found to affect different features of the network allowing for the identification and quantification of the noise. These features are then used as a guide toward different strategies for the compensation of the noise, and to examine how the compensation strategies perform. The results show that in general, modular networks are more robust to noise than monolithic ones.